2012
DOI: 10.1111/j.1600-0625.2012.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected variants of the steroid‐5‐alpha‐reductase isoforms SRD5A1 and SRD5A2 and the sex steroid hormone receptors ESR1, ESR2 and PGR: No association with female pattern hair loss identified

Abstract: Female pattern hair loss (FPHL) is a common disorder with a complex mode of inheritance. Although understanding of its etiopathogenesis is incomplete, an interaction between genetic and hormonal factors is assumed to be important. The involvement of an androgen-dependent pathway and sex steroid hormones is the most likely hypothesis. We therefore selected a total of 21 variants from the steroid-5-alpha-reductase isoforms SRD5A1 and SRD5A2, the sex steroid hormone receptors ESR1, ESR2 (oestrogen receptor) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The role of aromates genes CYP19A1) (15) has been reported but not confirmed in a more recent study (16). In other studies there were no associations between steroid 5-alpha-reductase isoforms genes or sex steroid hormone receptors and FPHL (17). Neither there was association with melanocortin 4 receptor gene (18).…”
Section: Etiopathogenesismentioning
confidence: 75%
“…The role of aromates genes CYP19A1) (15) has been reported but not confirmed in a more recent study (16). In other studies there were no associations between steroid 5-alpha-reductase isoforms genes or sex steroid hormone receptors and FPHL (17). Neither there was association with melanocortin 4 receptor gene (18).…”
Section: Etiopathogenesismentioning
confidence: 75%
“…Dear Editor , The aetiopathogenesis of female pattern hair loss (FPHL) is poorly understood. Although research has strongly implicated genetic factors in familial occurrence, no association finding for FPHL has yet been replicated . Consequently, no causal biological pathways can be suggested on the basis of currently available genetic findings.…”
Section: Association Analysis For Selected Markers At the Esr2 Gene Lmentioning
confidence: 99%
“…Recent studies have shown no involvement of the well-established locus on chromosome 20p11 in FPHL but have suggested that the androgen receptor/ectodysplasin A2 receptor (EDA2R) locus on the X chromosome confers susceptibility to early-onset FPHL [26]. In other studies, no association was found between steroid 5α-reductase isoform genes or sex steroid hormone receptors and FPHL [27]. Moreover, an Australian genome-wide association study suggested that the aromatase gene (CYP19A1) may contribute to FPHL, but this was not confirmed in another study [15,28].…”
Section: Discussionmentioning
confidence: 99%